Stellenwert der PSMA-Liganden-Bildgebung beim Prostatakarzinom - Gasch, Claudia; Kratochwil, Clemens; Vinsensia, Maria; Haberkorn, Uwe; Hadaschik, Boris; Giesel, Frederik L. (Der Urologe, 2017)
BackgroundProstate cancer (PCa) is one of the most common malignancies of men in developed countries. To improve clinical diagnostics of PCa, 68Ga-PSMA-11 was recently introduced as a new PET tracer. 68Ga-PSMA-11 is able to specifically bind to the prostate-specific membrane antigen (PSMA), which is upregulated on the surface of prostate cancer cells in most patients.ObjectivesTo analyse the current significance of 68Ga-PSMA-11 PET imaging in prostate cancer in relation to staging of men with initial diagnosis, biochemical recurrence and metastatic disease.Materials and methodsRetrospective analysis of current literature (PubMed search) regarding 68Ga-PSMA-11 PET diagnostics in primary staging, in biochemical recurrence and in metastasized disease.ResultsCompared to conventional imaging, 68Ga-PSMA-11 PET/CT reaches a higher sensitivity with an excellent specificity in the clinical diagnosis of primary staging as well as staging for recurrence and advanced, metastasized disease. In biochemical recurrence, 68Ga-PSMA-11 PET/CT shows significantly higher detection rates in comparison to choline PET/CT, especially in patients with low PSA values. In the clinical diagnosis of recurrent disease, therapy concepts were changed in more than a quarter of the patients due to the use of 68Ga-PSMA-11 PET/CT. The significance of staging with 68Ga-PSMA-11 PET/CT in advanced metastasized patients remains uncertain.ConclusionsDue to the excellent results of 68Ga-PSMA-11 PET imaging, even in patients with slightly elevated PSA levels, it will continue to play an important role in clinical diagnostics of prostate cancer and, thus, its clinical utilization will become more widely spread.
Online publiziert:22. Dezember 2016
Gesehen am 03.04.2018